Community perception and determinants of willingness to uptake COVID-19 vaccines among residents of Osun State, South-West Nigeria - Akinyemi, Patrick A.; Fajobi, Olusola; Owoade, Israel A.; Elugbaju, Olanrewaju T.; Wuraola, Funmilola O. (International Journal Of Community Medicine And Public Health, 2021)
Background: Vaccine has been identified as the most cost-effective way of fighting COVID-19 pandemic. As most countries await the COVID-19 vaccine for mass administration amidst numerous misconceptions, it is imperative to assess willingness of the masses to take the vaccine. This study aimed to assess the determinants of willingness to uptake COVID-19 vaccines among residents of Osun State. Methods: A descriptive cross-sectional study design was employed. Seven hundred and forty-four respondents were enrolled from three selected local government areas using a multistage sampling method. Interviewer administered questionnaire, structured based on the health belief model and social cognitive theory, in electronic format (Kobo Collect) was used for data collection. Determinants of willingness to take COVID-19 vaccine were assessed using binary logistic regression. Results: About three-quarters (59.1%) of the respondents were willing to take the vaccine. There was a significant association between positive perception and willingness to take COVID-19 vaccine, p<0.001. Being a healthcare worker, having good knowledge of the disease, and willingness-to-pay for the vaccine were significant determinants of willingness to uptake COVID-19 vaccine. Presence of misconception had a negative effect on the uptake of COVID-19 vaccine. Conclusions: To achieve high COVID-19 vaccine coverage, there is a need for health promotion interventions to correct misconceptions about COVID-19. Government and private donor interventions may be required to subsidize the vaccine to care for the populace who are willing to uptake but unable to pay for the vaccine.